Integrating the rent gap into the ground rent theory. Measurement and implications for different models of agriculture - Czyżewski, Bazyli; Lis, Piotr; Czyzewska, Izabela (Bulletin of Geography. Socio-economic Series, 2024)
The aim of this paper is to establish a conceptual framework for the rent gap theory in agriculture and to identify potential implications of the rent gap for socio-economic processes occurring in agriculture and rural areas. From an empirical perspective an attempt was made to determine the state and dynamics of the rent gap phenomenon in agriculture in Poland, considering the regional division. The authors used income approach and Capital Asset Pricing Model (CAPM) for estimating the capitalization rate. It was found that rent gap is a permanent phenomenon in Polish agriculture, the dynamics of which largely depends on macroeconomic factors. A widening rent gap may result in the withdrawal of land from farming and a decline in total factor productivity in agriculture. Thus, the implications of the rent gap may relate to food security. Measuring the rent gap can be a step towards determining the quasi-market value of environmental amenities of land.